Writing the Wrongs : Eva Valesh and the Rise of Labor Journalism - Faue, Elizabeth (Book collections on Project MUSE., 2002)
Compelling, insightful, and at times humorous, Writing the Wrongs is a window on the Progressive Era, on social history and the new journalism, and on women's lives and the meaning of class and gender."--Jacket